(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
This paper presents an in-depth analysis of contemporary alternative financing models for technology startups, emphasizing novel approaches such as crowdfunding, crowdinvesting, business angels, venture financing, and blockchain-based instruments like ICO. By integrating comparative research methods and case studies from both international and domestic contexts, the study explores the evolving landscape of startup financing amid constraints in traditional funding channels. The findings reveal that innovative financial strategies facilitate quicker capital access, risk diversification, and enhanced investor engagement. This work contributes to the theoretical framework and practical understanding of alternative financing, offering valuable insights for researchers, policymakers, and industry practitioners.